Influences of seed priming with Spirulina platensis extract on seed quality properties in black gram (Vigna mungo L.) - Thinh, Nguyen Quang (Vietnam Journal of Science, Technology and Engineering, 2021)
Black gram (Vigna mungo L.) is a high nutrient pulse crop. Its seed quickly and easily deteriorates after harvest, resulting in poor planting material production that must be improved accordingly by seed enhancement methods. The blue-green microalgae Spirulina platensis contains variously beneficial substances, including macro and micro nutrients, vitamins, amino acids and antioxidants. The aim of this study is to improve the vigour and germination of black gram by priming its seeds with Spirulina platensis extract to prevent seed deterioration. Medium vigour black gram seeds were subjected to hydropriming for three hours (T2); other seeds were primed with Spirulina platensis extract at 1.5% for three hours (T3) while unprimed seeds served as control (T1). Then, the seeds were artificially aged under 40±1oC and 95±5% relative humidity for five days. The results revealed that the hydropriming and control of black gram seeds were significantly lower in all physiological and biochemical seed quality parameters than seeds primed with Spirulina platensis extract at 1.5% for three hours. Consequently, Spirulina platensis extract can effectively enhance black gram seeds and use agents in.